Public Investment Management in Contexts of Fragility, Conflict & Violence – Part 2 - Cuvillier, Emmanuel (World Bank, Washington, DC, 2019)
The PIM Assessment resulted in the establishment of an Action Plan to strengthen the system. Given weak institutional capacity and limited resources, the Plan should include quick-win options where possible, particularly in the early recovery phase. Evidence shows that the process by which projects are delivered (scale, community involvement, expertise of project managers, etc.) can be more important than getting projects built quickly. This is an important balancing act to consider. A well-sequenced short-, medium- and long-term PIM Action Plan can be organized as follows: i) Formalize the institutional setting (establishing management functions inside the PIM cycle); ii) Develop capacity building in project design, appraisal and selection; iii) Improve capital investment project design, appraisal and selection; iv) Enhance the legal and regulatory framework of the PIM system; v) Improve process registration of projects via an Integrated Bank of Projects (IBP); vi) Establish regularly revisited project selection and prioritization criteria; vii) Formalize use of key performance indicators; and viii) Improve PIP–PPP in project management and ex-post evaluation.